2008
DOI: 10.1159/000155645
|View full text |Cite
|
Sign up to set email alerts
|

Orodigital Pemphigus Vulgaris: A Pathogenic Role of Anti-Desmoglein-3 Autoantibodies in Pemphigus Paronychia?

Abstract: Paronychia is a rare complication of pemphigus vulgaris (PV), and the immunological profile of patients with digital disease has not been assessed so far. We report 2 cases of PV with oral mucosa and periungual involvement, who had high titers of anti- desmoglein (Dsg)-3 circulating antibodies. These observations raise the possibility that expression of Dsg-1 and Dsg-3 in distinct areas of periungual skin is disease specific and that anti-Dsg-3 antibodies alone may have an as yet unrecognized importance for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…[ 1 ] It has been proposed that the autoantibodies against desmoglein 3 (Dsg3) alone may have a role in the development of paronychia in PV. [ 7 ] This supports the association of mucosal disease severity with nail changes in PV.…”
Section: Discussionsupporting
confidence: 73%
“…[ 1 ] It has been proposed that the autoantibodies against desmoglein 3 (Dsg3) alone may have a role in the development of paronychia in PV. [ 7 ] This supports the association of mucosal disease severity with nail changes in PV.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, this is not the case in nails, where both DSG1 and DSG3 are expressed at low level due to the absence of granular layer in nail matrix and thickness (2–3 cell layers) of nail bed epithelium ( 57 ). Thus, only high titers of anti-DSG1/anti-DSG3 or anti-DSG3 autoantibodies alone cause the collapsing of “immune privilege” and PV nail apparatus involvement ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the local expression of Dsg1 and Dsg3 is low, and only high concentrations of autoantibodies against desmosomal glycoproteins lead to involvement of the nail in PV [23]. In contrast, Laffitte et al [24] suggested that expression of Dsg1 and Dsg3 in the periungual skin is disease specific, and autoantibodies against Dsg3 alone may have a role in the development of paronychia in PV.…”
Section: Discussionmentioning
confidence: 99%